Production of secondary metabolites under challenging environments: understanding functions and mechanisms of signalling molecules - Sana,; Aftab, Tariq; Naeem, M.; Jha, Prakash Kumar; Prasad, P. V. Vara (Frontiers in Plant Science, 2025)
Plants are sessile organisms confronted by various abiotic stresses, including drought, salinity, heavy metals (HMs), and high/low temperatures throughout their growth cycles. In response to stress conditions, plants activate a cascade of metabolites and signalling molecules and networks. These intricate networks of signalling molecules like nitric oxide (NO), hydrogen sulfide (H2S), methyl jasmonate (MeJA), hydrogen peroxide (H2O2), ethylene (ETH), melatonin (MT), and calcium (Ca2+), play a crucial role in enhancing the production of secondary metabolites (SMs) in plants. In plants, SMs are characterized by four diverse groups’ terpenes, phenolics, alkaloids, and glucosinolates. Various environmental factors and plant developmental stages influence the production of SMs. The production and regulation of terpenes, phenolics, alkaloids, and glucosinolates in response to signalling molecules under stressed conditions provide valuable insights into stress tolerance. These insights are crucial for developing agricultural practices that improve crop resilience. They are essential for plants to cope with oxidative stress by providing defence mechanisms for improved adaptation, tolerance, and resilience strategies. Conversely, the crosstalk among the signalling molecules paves the way for new research avenues of plant stress management. This review emphasizes the essential role of SMs in plants and how the signalling molecules regulate their production under stress conditions. It also provides valuable insights into the mechanisms that facilitate plant adaptation and stress resilience.